Mica-based fireproof material for new energy automobile battery
By using mica-based fireproof materials in new energy vehicle batteries, combined with mica layer and modified graphene polyurethane coating, the problems of increased weight and insufficient fire resistance of existing fireproof materials are solved, and excellent fire resistance, waterproof and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411781197.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-14
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The fire-resistant materials of existing new energy vehicle batteries are relatively large, resulting in an increase in the weight of the battery module and further improvement in the fire resistance performance. At the same time, the battery installation location is susceptible to rainwater and mud, which poses a risk of corrosion.
Mica-based fire-resistant materials are used, including mica layers and waterproof coatings. The mica layer is made of mixing mica and adhesive at a weight ratio of 100:15-25, and the waterproof coating imparts hydrophobic and anticorrosive properties to the material through the synthesis of modified graphene and polyurethane.
It achieves excellent fire resistance of battery components, alleviates safety hazards after thermal runaway, and gives good waterproof and corrosion resistance, improving the durability of overall performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fireproof materials, and in particular to a mica-based fireproof material for new energy vehicle batteries. Background Art
[0002] At present, with the continuous expansion of the market demand for new energy vehicles such as pure electric vehicles and hybrid electric vehicles, the demand for batteries is also increasing. However, electric vehicles can easily cause thermal airflow due to problems such as thermal runaway of batteries, which can easily cause damage to the inside of the battery pack and cause other units of the battery pack to burn, thereby causing damage to other parts of the car and operators. Therefore, generally, by setting a protective device outside the battery assembly, it can effectively protect and delay damage to operators and other components. However, in the prior art, the fireproof material used in such protective devices is generally thicker, which increases the weight of the entire battery assembly, and its fireproof performance needs to be further improved.
[0003] Moreover, the batteries of new energy vehicles are mostly installed under the floor of the vehicle body. The location where the batteries are installed is more easily exposed to rain, mud, etc., and is a severely affected area by corrosion. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a mica-based fireproof material for new energy vehicle batteries.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A mica-based fireproof material for new energy vehicle batteries, comprising a mica layer and a waterproof coating, wherein the mica layer is formed by mixing mica and an adhesive in a weight ratio of 100:15-25; The waterproof coating is made by the following steps: Step S1, adding graphene and 3-mercaptopropyl-trimethoxysilane to a 15% volume fraction ethanol aqueous solution, heating to 40-45° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified graphene, and controlling the amount ratio of graphene, 3-mercaptopropyl-trimethoxysilane and ethanol aqueous solution to be 1-2 g: 3-5 g: 15-20 mL; In step S1, 3-mercaptopropyl-trimethoxysilane is used as a silane coupling agent and then hydrolyzed to condense with hydroxyl groups on the graphene surface, and then grafted onto the graphene surface to introduce mercapto groups; Step S2, (refer to the synthesis and application of 2,6,2′,6′-tetraallylbisphenol A, School of Chemistry and Molecular Engineering, Zhengzhou University) 2,6,2',6'-tetraallylbisphenol A and modified graphene are added to tetrahydrofuran, initiator 1173 is added, stirred evenly, and placed under ultraviolet light 365nm for reaction at room temperature for 30min, then 1H,1H,2H,2H-perfluorodecanethiol is added, and the reaction is continued under ultraviolet light 365nm for 30min, and the solvent is removed by rotary evaporation to obtain modified graphene, wherein the amount ratio of modified graphene, 2,6,2',6'-tetraallylbisphenol A, 1H,1H,2H,2H-perfluorodecanethiol and tetrahydrofuran is controlled to be 1-2g:10-15mmol:30-50mmol:50mL, and the amount of initiator 1173 is 3-5% of the weight of the modified graphene; In step S2, the thiol groups on the modified graphene first react with the carbon-carbon double bonds on 2,6,2',6'-tetraallyl bisphenol A, and then 1H,1H,2H,2H-perfluorodecanethiol is added, and the carbon-carbon double bonds that do not participate in the reaction react with the thiol groups on 1H,1H,2H,2H-perfluorodecanethiol, thereby preparing modified graphene. A large amount of fluorine elements on 1H,1H,2H,2H-perfluorodecanethiol are introduced into the modified graphene, and a dihydroxy structure on 2,6,2',6'-tetraallyl bisphenol A is also introduced.
[0006] Step S3, adding polytetrahydrofuran and hexamethylene diisocyanate to N, N-dimethylformamide, stirring at a uniform speed and reacting for 1.5h, then adding modified graphene and dibutyl tin dilaurate, continuing stirring and reacting for 2h to obtain modified polyurethane, controlling the amount ratio of polytetrahydrofuran, hexamethylene diisocyanate, modified graphene, dibutyl tin dilaurate and N, N-dimethylformamide to be 5-10mmol: 5-8mmol: 1-1.5g: 0.01-0.03g: 50mL; The dihydroxy structure on the modified graphene in step S3 can act as a chain extender to connect the graphene to the polyurethane structure. Connecting the graphene to the matrix through chemical reaction can improve the binding force between the fluorine element on the surface of the graphene and the matrix, while giving the polyurethane matrix hydrophobic properties, the hydrophobic durability of the polyurethane coating is improved. Moreover, due to the functional characteristics of the polyurethane itself, the coating can be given excellent anti-corrosion properties.
[0007] Step S4, by weight, add 35-50 parts of modified polyurethane to 100 parts of deionized water, stir at a uniform speed for 30 minutes, then add 0.2-0.5 parts of wetting agent, 0.3-0.5 parts of defoaming agent, and 0.2-0.3 parts of leveling agent in sequence, stir evenly, and then coat the surface of the mica layer to obtain a waterproof coating.
[0008] Furthermore, the adhesive is an epoxy resin adhesive or a silicone resin adhesive.
[0009] Beneficial effects of the present invention: The invention prepares a mica-based fireproof material for a new energy vehicle battery, comprising a mica layer and a waterproof coating. The mica layer gives the battery excellent fireproof performance, prevents flame burning caused by thermal runaway of the battery, and effectively alleviates the potential safety hazard after thermal runaway of the battery. The waterproof coating is provided to give the battery good waterproof and corrosion resistance. In the preparation process of the waterproof coating, modified graphene is first prepared, a large amount of fluorine elements on 1H, 1H, 2H, 2H-perfluorodecanethiol are introduced into the modified graphene, and a dihydroxy structure on 2, 6, 2', 6'-tetraallyl bisphenol A is also introduced. The dihydroxy structure on the modified graphene can be used as a chain extender to connect the graphene to a polyurethane structure, and the graphene is connected to a matrix through a chemical reaction, so as to improve the bonding force between the fluorine element on the graphene surface and the matrix, and at the same time, the hydrophobic performance of the polyurethane matrix is given, and the hydrophobic durability of the polyurethane coating is improved. In addition, due to the functional characteristics of the polyurethane itself, the coating can be given excellent anti-corrosion performance. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0011] A mica-based fireproof material for new energy vehicle batteries, comprising a mica layer and a waterproof coating, wherein the mica layer is formed by mixing mica and an adhesive in a weight ratio of 100:15; The waterproof coating is made by the following steps: Step S1, adding graphene and 3-mercaptopropyl-trimethoxysilane to a 15% volume fraction ethanol aqueous solution, heating to 40°C, stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified graphene, and controlling the amount ratio of graphene, 3-mercaptopropyl-trimethoxysilane and ethanol aqueous solution to be 1g:3g:15mL; Step S2, (refer to the synthesis and application of 2,6,2′,6′-tetraallylbisphenol A, School of Chemistry and Molecular Engineering, Zhengzhou University) 2,6,2',6'-tetraallylbisphenol A and modified graphene are added to tetrahydrofuran, initiator 1173 is added, stirred evenly, and placed under ultraviolet light 365nm for reaction at room temperature for 30min, then 1H,1H,2H,2H-perfluorodecanethiol is added, and the reaction is continued under ultraviolet light 365nm for 30min, and the solvent is removed by rotary evaporation to obtain modified graphene, wherein the amount ratio of modified graphene, 2,6,2',6'-tetraallylbisphenol A, 1H,1H,2H,2H-perfluorodecanethiol and tetrahydrofuran is controlled to be 1g:10mmol:30mmol:50mL, and the amount of initiator 1173 is 3% of the weight of the modified graphene; Step S3, adding polytetrahydrofuran and hexamethylene diisocyanate to N, N-dimethylformamide, stirring at a uniform speed and reacting for 1.5h, then adding modified graphene and dibutyltin dilaurate, continuing stirring and reacting for 2h to obtain modified polyurethane, controlling the amount ratio of polytetrahydrofuran, hexamethylene diisocyanate, modified graphene, dibutyltin dilaurate and N, N-dimethylformamide to be 5mmol: 5mmol: 1g: 0.01g: 50mL; Step S4, by weight, add 35 parts of modified polyurethane to 100 parts of deionized water, stir at a uniform speed for 30 minutes, then add 0.2 parts of wetting agent, 0.3 parts of defoaming agent, and 0.2 parts of leveling agent in sequence, stir evenly, and then coat the surface of the mica layer to obtain a waterproof coating.
[0012] The defoamer is KS-604, the wetting agent is OP-340, and the leveling agent is BYK-337.
[0013] The adhesive is an epoxy resin adhesive or a silicone resin adhesive. Example
[0014] A mica-based fireproof material for new energy vehicle batteries, comprising a mica layer and a waterproof coating, wherein the mica layer is formed by mixing mica and an adhesive in a weight ratio of 100:20; The waterproof coating is made by the following steps: Step S1, adding graphene and 3-mercaptopropyl-trimethoxysilane to a 15% volume fraction ethanol aqueous solution, heating to 42° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified graphene, and controlling the amount ratio of graphene, 3-mercaptopropyl-trimethoxysilane and ethanol aqueous solution to be 1.5 g:4 g:18 mL; Step S2, (refer to the synthesis and application of 2,6,2′,6′-tetraallylbisphenol A, School of Chemistry and Molecular Engineering, Zhengzhou University) 2,6,2',6'-tetraallylbisphenol A and modified graphene are added to tetrahydrofuran, initiator 1173 is added, stirred evenly, and placed under ultraviolet light 365nm for reaction for 30min at room temperature, then 1H,1H,2H,2H-perfluorodecanethiol is added, and the reaction is continued under ultraviolet light 365nm for 30min, and the solvent is removed by rotary evaporation to obtain modified graphene, wherein the amount ratio of modified graphene, 2,6,2',6'-tetraallylbisphenol A, 1H,1H,2H,2H-perfluorodecanethiol and tetrahydrofuran is controlled to be 1.5g:12mmol:40mmol:50mL, and the amount of initiator 1173 is 4% of the weight of the modified graphene; Step S3, adding polytetrahydrofuran and hexamethylene diisocyanate to N, N-dimethylformamide, stirring at a uniform speed and reacting for 1.5h, then adding modified graphene and dibutyltin dilaurate, continuing stirring and reacting for 2h to obtain modified polyurethane, controlling the amount ratio of polytetrahydrofuran, hexamethylene diisocyanate, modified graphene, dibutyltin dilaurate and N, N-dimethylformamide to be 8mmol:6mmol:1.2g:0.02g:50mL; Step S4, by weight, add 45 parts of modified polyurethane to 100 parts of deionized water, stir at a uniform speed for 30 minutes, then add 0.4 parts of wetting agent, 0.4 parts of defoaming agent, and 0.2 parts of leveling agent in sequence, stir evenly, and then coat the surface of the mica layer to obtain a waterproof coating.
[0015] The defoamer is KS-604, the wetting agent is OP-340, and the leveling agent is BYK-337.
[0016] The adhesive is an epoxy resin adhesive or a silicone resin adhesive. Example
[0017] A mica-based fireproof material for new energy vehicle batteries, comprising a mica layer and a waterproof coating, wherein the mica layer is formed by mixing mica and an adhesive in a weight ratio of 100:25; The waterproof coating is made by the following steps: Step S1, adding graphene and 3-mercaptopropyl-trimethoxysilane to a 15% volume fraction ethanol aqueous solution, heating to 45°C, stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified graphene, and controlling the amount ratio of graphene, 3-mercaptopropyl-trimethoxysilane and ethanol aqueous solution to be 2g:5g:20mL; Step S2, (refer to the synthesis and application of 2,6,2′,6′-tetraallylbisphenol A, School of Chemistry and Molecular Engineering, Zhengzhou University) 2,6,2',6'-tetraallylbisphenol A and modified graphene are added to tetrahydrofuran, initiator 1173 is added, stirred evenly, and reacted under ultraviolet light of 365 nm at room temperature for 30 min, then 1H,1H,2H,2H-perfluorodecanethiol is added, and the reaction is continued under ultraviolet light of 365 nm for 30 min, and the solvent is removed by rotary evaporation to obtain modified graphene, wherein the amount ratio of modified graphene, 2,6,2',6'-tetraallylbisphenol A, 1H,1H,2H,2H-perfluorodecanethiol and tetrahydrofuran is controlled to be 2 g:15 mmol:50 mmol:50 mL, and the amount of initiator 1173 is 5% of the weight of the modified graphene; Step S3, adding polytetrahydrofuran and hexamethylene diisocyanate to N, N-dimethylformamide, stirring at a uniform speed and reacting for 1.5h, then adding modified graphene and dibutyltin dilaurate, continuing stirring and reacting for 2h to obtain modified polyurethane, controlling the amount ratio of polytetrahydrofuran, hexamethylene diisocyanate, modified graphene, dibutyltin dilaurate and N, N-dimethylformamide to be 10mmol: 5-8mmol: 1.5g: 0.03g: 50mL; Step S4, by weight, add 50 parts of modified polyurethane to 100 parts of deionized water, stir at a uniform speed for 30 minutes, then add 0.5 parts of wetting agent, 0.5 parts of defoaming agent, and 0.3 parts of leveling agent in sequence, stir evenly, and then coat the surface of the mica layer to obtain a waterproof coating.
[0018] The defoamer is KS-604, the wetting agent is OP-340, and the leveling agent is BYK-337.
[0019] The adhesive is an epoxy resin adhesive or a silicone resin adhesive.
[0020] Comparative Example 1 Compared with Example 1, this comparative example uses a commercially available hydrophobic polyurethane coating (filler is graphene) instead of the waterproof coating of the present invention.
[0021] The performance of the waterproof coatings prepared in Examples 1-3 and Comparative Example 1 was tested, and the results are shown in Table 1 below: Water resistance: The water resistance test is carried out according to GB 1722-79 (88) standard.
[0022] Table 1
[0023] The fireproof materials prepared in Examples 1-3 were subjected to heat resistance tests, and the test results are shown in Table 2, wherein the baking experiment is to bake the prepared fireproof materials at 500° C. for 2 h.
[0024] Table 2
[0025] It can be seen from Tables 1 and 2 above that the fireproof material prepared by the present invention has excellent heat resistance and fireproof performance, and has good water resistance.
[0026] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A mica-based fireproof material for new energy vehicle batteries, characterized in that: Comprising a mica layer and a waterproof coating, wherein the mica layer is mixed with mica and an adhesive in a weight ratio of 100:15-25; The waterproof coating is made by the following steps: Step S1, adding graphene and 3-mercaptopropyl-trimethoxysilane to a 15% by volume ethanol aqueous solution, heating to 40-45° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified graphene; Step S2, adding 2,6,2',6'-tetraallylbisphenol A and modified graphene to tetrahydrofuran, adding an initiator, stirring evenly, and reacting under ultraviolet light at room temperature for 30 minutes, then adding 1H,1H,2H,2H-perfluorodecanethiol, continuing to react under ultraviolet light for 30 minutes, and rotary evaporating the solvent to obtain modified graphene; Step S3, adding polytetrahydrofuran and hexamethylene diisocyanate to N, N-dimethylformamide, stirring at a uniform speed and reacting for 1.5h, then adding modified graphene and dibutyltin dilaurate, continuing to stir and react for 2h to obtain modified polyurethane; Step S4, by weight, add 35-50 parts of modified polyurethane to 100 parts of deionized water, stir at a uniform speed for 30 minutes, then add 0.2-0.5 parts of wetting agent, 0.3-0.5 parts of defoaming agent, and 0.2-0.3 parts of leveling agent in sequence, stir evenly, and then coat the surface of the mica layer to obtain a waterproof coating.
2. A mica-based fireproof material for new energy vehicle batteries according to claim 1, characterized in that: In step S1, the amount ratio of graphene, 3-mercaptopropyl-trimethoxysilane and ethanol aqueous solution is controlled to be 1-2 g: 3-5 g: 15-20 mL.
3. A mica-based fireproof material for new energy vehicle batteries according to claim 1, characterized in that: In step S2, the amount ratio of modified graphene, 2,6,2',6'-tetraallylbisphenol A, 1H,1H,2H,2H-perfluorodecanethiol and tetrahydrofuran is controlled to be 1-2 g:10-15 mmol:30-50 mmol:50 mL, and the amount of initiator (1173) is 3-5% of the weight of the modified graphene.
4. A mica-based fireproof material for new energy vehicle batteries according to claim 1, characterized in that: In step S3, the dosage ratio of polytetrahydrofuran, hexamethylene diisocyanate, modified graphene, dibutyltin dilaurate and N,N-dimethylformamide is controlled to be 5-10mmol:5-8mmol:1-1.5g:0.01-0.03g:50mL.
5. The mica-based fireproof material for new energy vehicle batteries according to claim 1, characterized in that: The adhesive is an epoxy resin adhesive or a silicone resin adhesive.
Citation Information
Patent Citations
Fireproof material used for batteries as well as preparation method and application of fireproof material
CN109987884A
Graphene modified polyurethane super-hydrophobic anticorrosive material and preparation method thereof
CN111334177A
Water-based anti-corrosive coating and preparation method thereof
CN112708297A
Washable printing ink and printing process thereof
CN116589881A
Anticorrosive Grafted Graphene Filler for Organic Coating and Methods of Preparing the Same
US20200239708A1
Cited By
Fireproof coating for new energy battery and preparation method of fireproof coating
CN120737724A